A randomized pilot study of mindfulness‐based stress reduction in a young adult cancer sample: Feasibility, acceptability, and changes in patient reported outcomes. Issue 5 (25th February 2020) - Victorson, David; Murphy, Karly; Benedict, Catherine; Horowitz, Bruriah; Maletich, Carly; Cordero, Evelyn; Salsman, John M.; Smith, Kristin; Sanford, Stacy
Abstract: Background: The primary purpose of this study was to examine the feasibility and acceptability of participation in a randomized waitlist‐controlled intervention of mindfulness‐based stress reduction (MBSR) in a young adult cancer sample. A secondary aim was to examine patterns of change in patient reported outcomes (PROs) of physical, social, and emotional functioning. Methods: Participants were enrolled at a large Midwestern comprehensive cancer center and randomized to MBSR or a waitlist control. Feasibility and acceptability were examined through enrollment metrics and a survey. PROs were gathered at baseline, 8‐weeks, and 16‐weeks. Descriptive statistics and mixed models were used in analyses. Results: Of 597 eligible participants, 151 (26.5%) consented from which 126 (83.4%) completed baseline measures. Sixty‐seven participants were randomized to MBSR, and 59 to the waitlist. Immediately following MBSR, the majority of respondents (72%‐78%) reported their experience with mindfulness was very logical and useful to increasing their wellbeing. Compared to waitlist members, MBSR participant's scores on PROs improved in expected directions. Conclusions: Our findings suggest that recruitment for an intensive, in‐person, multi‐week supportive intervention can be challenging with young adults with cancer, similar to other cancer survivor populations; however once enrolled, feasibility and acceptability of MBSR was supported. Further, initial evidence on the role of MBSR on short‐term changes in select PROs with this population was also demonstrated.